Bureaucratic and Political Corruption: The Nexus between Corrupt Politicians and Bureaucrats: A Threat to National Integrity and Safety (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Today, corruption has become the root-cause of danger for the integrity and safety of the nation. It may be seen in the recent encounter with terrorists in the Mumbai where three brave and intelligent police officers were shot dead by the terrorists. Report says that purchasing of Bullet Proof Jackets has the smell of corruption. Indeed it is the peak point of the corruption. Our past also has the long list of big scams, it started with Jeep scam in Nehru regime and now continue with all kinds of corruption in every field of the government. There is hardly left any department or state government which did not indulge in malfunctioning or corruption in the country, the amount kept in the Swiss Bank is giving the full proof of the corruption. Corruption starts at top in the political community and it patronizes the administration. In India there is a deep rooted nexus between the corrupt politicians and the corrupt bureaucrats. Politicians appoint the bureaucrats as per their self-interests not for the requirement of administration or developmental activities. We have had many cases in which bureaucrats with well-publicized reputation for corruption were appointed to topmost posts super ceding other honest officers. There have also been cases in which politicians and bureaucrats have been charged together in corruption cases.(1) After this, it bears others factors for generating the corruption like lack of transparency and accountability inadequate people participation frequent transfers of the civil servants nepotism and favouritism in the appointments of the top posts especially in the states low remuneration, facilities and over workload of the officials absence of e-governance, unawareness of RTI Act inadequate status of CVC and malfunctioning of SPSCs.